2017
DOI: 10.1177/1403494817690940
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in subjective health complaints in adolescence: The roles of self-esteem, stress from schoolwork and body dissatisfaction

Abstract: The findings showed that self-esteem and stress from schoolwork were associated with subjective health complaints during adolescence. These factors could partially explain the excess of subjective health complaints among girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
23
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 26 publications
13
23
0
4
Order By: Relevance
“…Either there are additional factors affecting their self-esteem, or they does not posses enough introspective competences to perform detailed, rational and objective evaluation of themselves, despite being on a course of physical education, which should be the most appropriate higher education course of such competences. This study could support hypothesis, that education could emphasise health behaviours and nullify gender differences regarding self-esteem exposed in other studies (Aanesen, Meland, & Torp, 2017).…”
Section: Sd -Standard Deviationsupporting
confidence: 85%
“…Either there are additional factors affecting their self-esteem, or they does not posses enough introspective competences to perform detailed, rational and objective evaluation of themselves, despite being on a course of physical education, which should be the most appropriate higher education course of such competences. This study could support hypothesis, that education could emphasise health behaviours and nullify gender differences regarding self-esteem exposed in other studies (Aanesen, Meland, & Torp, 2017).…”
Section: Sd -Standard Deviationsupporting
confidence: 85%
“…Female students do not necessarily enjoy school more than male students, but they might work and try harder and have goals of performing better academically than male students do. If female students do work harder, this effort could be related to female adolescents' higher levels of subjective health complaints (SHC) as well as the association between SHC and stress from schoolwork and lower levels of self-esteem (Aanesen, Meland, & Torp, 2017). This topic is important, and teachers' support is a protective and reducing factor for such complaints (e.g., Ghandour, Overpeck, Huang, Kogan, & Scheidt, 2004).…”
Section: Age Gender and Student Engagementmentioning
confidence: 99%
“…On the other hand, numerous published studies have described health ailments among school youth. A Norwegian study showed a significantly higher prevalence of headaches, neck pain, back pain and abdominal pain among girls when compared to boys [23], and many other studies have confirmed the higher prevalence of subjective health ailments among girls when compared to boys [24,25]. Ravens-Sieberer and collaborators [26] have also reported that the gender differences in subjective health ailments in children and adolescents increase with age, and researchers have identified an inverse correlation between health ailments and socioeconomic status.…”
Section: Girlsmentioning
confidence: 96%
“…Ravens-Sieberer and collaborators [26] have also reported that the gender differences in subjective health ailments in children and adolescents increase with age, and researchers have identified an inverse correlation between health ailments and socioeconomic status. Moreover, studies have shown a clear correlation between low self-esteem and high levels of stress and subjective health ailments [23,24,27]. Even though most of the studies mentioned above focus on youth who are in education, we believe there is reason to assume that young people who are not in education or employment may have just as low self-esteem, high levels of stress and health problems.…”
Section: Girlsmentioning
confidence: 99%